Strategies for fast scanning, ranging and handovers in WiMAX/802.16. (6th November 2008) - Boone, Paul; Barbeau, Michel; Kranakis, Evangelos
In WiMAX/IEEE 802.16 with mobility support, the network entry procedure for a mobile station involves several steps including the scanning for an available channel and performing initial ranging in order to determine power and timing offset requirements. These steps are performed by a mobile station at start up or when about to perform a handover and must be done promptly in order to reduce delays in network access or possible dropped connections. We propose strategies that a mobile station can use to reduce the time required for scanning and ranging operations while attempting to establish network connectivity or perform a handover between neighbouring base stations. We model and simulate an area of WiMAX coverage using real-world mobility trace data and show that there are strategies that reduce the time required for scanning and ranging operations significantly.